Pengaruh Kegiatan Ekstrakurikuler terhadap Motivasi Belajar Siswa di SMP Muhammadiyah 02 Medan - Fella Annisa Harahap; Muhammad Rifa’i; Yusuf Hadijaya (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to evaluate the influence of extracurricular activities on students' learning motivation at SMP Muhammadiyah 02 Medan. Extrinsic motivation is often needed to encourage students who lack an internal drive to learn, especially at elementary school age, where play activities are often more interesting than learning. It is hoped that extracurricular activities can function as a source of additional motivation and improve student learning outcomes. This research uses a quantitative approach with a survey method, where data is collected through questionnaires and analyzed using SPSS 25.0. The research results show that the significance value of the t test for the extracurricular activity variable is 0.000, which is smaller than 0.05, and the calculated t of 1.848 is smaller than the t table of 2.052. Thus, the hypothesis that extracurricular activities influence learning motivation. The coefficient of determination (R²) of 0.112 indicates that only 11.2% of the variation in learning motivation can be explained by extracurricular activities, while the remainder (88.8%) is influenced by other factors outside this research. These findings indicate that although extracurricular activities are an important element, their influence on students' learning motivation at SMP Muhammadiyah 02 Medan is not significant.